Venture-backed IPOs and the exiting of venture capital in China - Xiaoqing Eleanor Xu (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
This paper documents the dramatic improvement in institutional, legal and regulatory environment for the exiting of foreign venture capital in China. It also discusses the recent developments, advantages and disadvantages of various China venture-backed IPO listing channels, including overseas listing through the main board and high-tech trading board in the United States (via New York Stock Exchange and NASDAQ), Hong Kong (via Hong Kong Stock Exchange and Hong Kong Growth Enterprise Market) and Singapore (via Singapore Exchange and SESDAQ), and domestic listing (via Shenzhen Small and Medium Enterprise Board). Finally, this paper examines the venture capital funding and IPO offering details, and the short-run and long-run performance of the U.S.-listed China Venture-backed IPOs between 2000 and 2005.
Keywords: 650